Assessment of outcomes after intralesional bleomycin sclerotherapy of lymphatic malformations in children - Mazhar, Aqsa; Shazlee, Muhammad Kashif; Mallick, Yousuf Abd; Muhammad, Ammar Ali; Samad, Lubna (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the efficacy of bleomycin in the treatment of lymphatic malformations, and the concordance between photographic and radiological assessments of the outcome. Method: The retrospective study was conducted at the Vascular Anomalies Centre of Indus Hospital, Karachi, and comprised data of patients enrolled with diagnosis of macrocystic or mixed lymphatic malformations from January 2017 to November 2019. All patients had been treated with injection bleomycin 0.6-1mg/kg/session. Size and location of lesions, ultrasonographic findings, photographic documentation and post-procedure complications were reviewed. Photographic and radiographical assessment outcomes were categorised as excellent, good or poor, and compared for concordance. Data was analysed using Stata 14. Results: Of the 31 children, 22(68.8%) were boys. Mean age at presentation was 54.2±44 months (range: 2 months to 15.7 years). There were 32 lymphatic malformations; 29(90.6) macrocystic and 3(9.4%) mixed. Head and neck region was mostly involved 19(59.4%). Most lesions 23(71.9%) presented during the first year of life, and 29(90.6%) lesions were purely macrocystic. Excellent, good and poor response was seen in 16(50%), 15(46.9%) and 1(3.1%) lesions on photographic assessment, and 21(65.6%), 11(34.4%) and 0(0.0%) lesions on radiological assessment, respectively. Concordance in photographic and radiological outcomes was 22(69%). No complications were seen and no statistically significant difference was observed for photographic and radiographic assessment with respect to gender, malformation type, region involved, and number of sessions (p>0.05). Conclusion: Intralesional bleomycin sclerotherapy was found to be effective in the treatment of lymphatic malformations. Clinical observation was reliable in assessing progress on routine follow-up, with additional radiology done when management decisions needed to be reviewed. Key Words: Bleomycin, Intralesional injection, Lymphatic malformations, Sclerotherapy.